Detection and Frequency of Lily Viruses in Argentina - Chinestra, Silvia Carolina (2010)
In a survey of lily growing fields in various regions of Argentina, three viruses, Lily symptomless virus (LSV), Lily mottle virus (LMoV), and Cucumber mosaic virus (CMV), were found in Longiflorum, Asiatic, Oriental, Longiflorum × Asiatic (LA), and Oriental × Trumpet (OT) hybrids. The areas surveyed were between latitude 26° 56′ S and 43° 03′ S, and longitude 65° 21′ W and 71° 29′ W. Virus detection was performed by double-antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA) using polyclonal antiserum. In infected samples, viruses detected in decreasing order were LSV (60.5%), LMoV (51.0%), and CMV (28.7%) present in single or mixed infections. Virus infection varied among tested hybrids from 36.0% (Oriental Montecristo) to 94.7% (Lilium longiflorum Avita) in 2006 and from 38.9% (OT Yelloween) to 82.1% (LO Triumphator) in 2007, with an overall incidence of 64.1 and 70.7% in 2006 and 2007, respectively. A variation in virus incidence among localities was also observed. The highest virus incidence (89.6 and 87.6% in 2006 and 2007, respectively) was observed in Bahía Blanca (38° 44′ S, 62° 16′ W). The lowest virus incidences, detected in Trevellin (43° 03′ S, 71° 29′ W) and in Malargüe (35° 28′ S, 69° 35′ W), were 47.4 and 48.6% in 2006 and 2007, respectively. Moreover, a different distribution of each virus was observed between localities. The high occurrence of viruses infecting lily crops in Argentina could be due to both the use of infected bulbs for propagation and the lack of preventive virus vector control measures.